Effect of Hub-to-tip Ratio on Performance of High Speed Pump-jet Propulsor for Undersea Vehicle - Gongchang GAN (水下无人系统学报)
To investigate the influence of the hub-to-tip ratio on the high-speed pump-jet propulsors of undersea vehicles, this study took an impeller with specific speed of 1 920 as the research object and conducted numerical calculation, performance result analysis and comparison, and experimental verification of three different hub-to-tip ratios of a high-speed pump-jet propulsor for undersea vehicles. Using Fluent software, it adopted a Reynolds-averaged N-S equation and an shear stress transport k-ω model to predict the head, efficiency, and thrust of the impeller. The performance curves, cavitation performance data, and internal flow field conditions of the impeller under different hub-to-tip ratios were obtained through numerical simulation calculations. The results show that the pressure gradient on the blade surface from the blade tip to the rim decreases. With the increase in the hub-to-tip ratio, the maximum static pressure on the blade and the head and efficiency of the pump-jet propulsor all decrease, and the cavitation performance significantly declines. However, the cavitation state is superior to that at the small hub-to-tip ratio. The research findings can provide certain reference for the structure optimization design of high-speed pump-jet propulsors for undersea vehicles.